The Analysis Of The Push-sum Protocol In Various Distributed Systems - Martin Kenyeres; Jozef Kenyeres; Vladislav Skorpil (European Scientific Journal, ESJ, 2016)
In this paper, we have focused on an analysis of the push-sum protocol in various topologies. We analyzed the behavior of distributed systems forming a tree, a star, a ring and a fully-connected mesh topology. We also examined the influence of stochastic features of the push-sum protocol on the properties of this protocol and the convergence rates in the particular topologies.